Dirty customers: Stigma and identity among sex tourists. (February 2018) - Neal, Mark
This article asks the question, "How do Western men who travel to Thailand to pay for sex with Thai women morally justify their actions?" In order to answer this, the study frames the question in terms of debates about "dirty work" and introduces the concept of "dirty customers" to analyze sex tourists and to highlight the potential stigma and moral taint involved in their engagement with sex workers. The research methodology involved content analysis of website discourse among Western men who visit Thailand for paid sex; examining their discussions and debates, and thereby identifying key themes and patterns in their exchanges. The study found that although sex work can arguably be categorized as "dirty work, " sex tourists resist such characterizations of sex work and of their role in it. The article thereby analyses how sex tourist discourse neutralizes external moralities of stigma and shame. It shows why neutralization is significant for understanding how sex tourism is sustained as an industry and how it is significant at the theoretical level for our understanding of "dirty work" and "dirty customers" as analytical concepts.